The ambiguity of existence in Merleau-Ponty - Álvarez González, Eduardo (Estudios de Filosofía, 2011)
The actual piece deals with the new sense conferred to Human Existence by Merleau-Ponty, that as it simultaneously recognizes its belonging to the world according to the heideggerian notion of beingin the-world and from a viewpoint that opposes Rationalist Intellectualism, nevertheless does not renounce a Philosophy of the Subject inspired in the later Husserl. This approach leads Merleau-Ponty to interpret the Cartesian Principle of cogito as Existence, and to attribute to this notion an ambiguity: that which corresponds to the double and simultaneous consideration of belonging to the world and being differentiated from it. This philosophical project is elaborated through a new way of describing experience in the line of a Phenomenological Conception which attributes to the Body the transcendental role that Classical Idealism assigned to Conscience